The Relationship of The Implementation of The Covid-19 Vaccine with The Level of Patient's Anxiety in The Work Area of Puskesmas “X” - Effendi Effendi; Fatima Nuraini Sasmita; Neni Triana; Wenny Hartati; Sanisahhuri Sanisahhuri; Ade Herman Surya Direja; Vike Pebri Giena (Universitas Aisyah Pringsewu, 2022)
Covid-19 is a coronavirus that is caused by the SARS-Cov-2 virus and affects both people who have been vaccinated and people who have not been vaccinated. It has been found in Indonesia. The goal of this study was to find out if there was a link between giving patients the COVID-19 vaccine and how anxious they were in the Karang Tinggi Health Center Work Area. This type of research is based on an analytical survey with a cross-sectional design and random sampling. Using a questionnaire sheet, collect data. The Chi-Square Test was used to get the results of the study from 54 people. There were 9 people (100%) who didn't get the COVID-19 vaccine. All of them had moderate anxiety, and none of them had mild anxiety. Also, 10 (22.2%) of the 45 people who got the COVID-19 vaccine had mild anxiety and 35 (77.8%) had moderate anxiety. Based on the study's findings, it can be seen that p = 0.183. Because the p value is greater than 0.05, Ho is accepted and Ha is not. This means that there is no significant link between the COVID-19 vaccine and how anxious patients are in the Karang Tinggi Health Center Work Area